'O Plato! Plato!': Don Juan versus the Philosophers. Issue 1 (1st June 2021) - Davis, William
Abstract : Critics who take Byron seriously as a thinker tend to locate his personal philosophy within the history of scepticism. In Cantos I and II of Don Juan, Byronic doubting takes the form of a critique of idealism, with a particular focus on Plato. This essay argues that Byron's scepticism has philosophical implications beyond the critique of Platonism, that it works also to undermine the major idealist movement of his day – German absolute idealism. Byron's embodied ethic is evident both in the narrator's comments and within the narrative of Juan's affair with Haidée. The form this critique of idealism takes anticipates Nietzsche's 'revaluation of values' as well as Derrida's deconstruction in that it isolates a traditionally hierarchised pair of oppositions and revalues the hierarchy.